The Attitude of the Electorate to Statutory Solutions Giving Equal Opportunity to Men and Women in Filling the Positions on Electoral Lists - Łukasik-Turecka, Agnieszka (Political Preferences, 2013)
The research carried out allowed to look at social assessment of both already implemented statutory quotas and the proposed gender parity on electoral lists. The findings of the research showed that over half of the surveyed left-wing political party-in-the-electorate acknowledged the implementation of statutory quotas as reasonable and the proposal of introducing gender parity on the electoral lists as worth-implementing (Palikot's Movement - 42.2% and Democratic Left Alliance - 37.9%). Among the Civic Platform and Polish People's Party adherents a substantial percentage are the adherents of quotas rather than gender parity (Civic Platform - 44.1% and 38.9% respectively, Polish People's Party - 48.7% i 34.2% respectively) but there are substantially fewer adversaries of this solution. At the same time among the adversaries of Law and Justice only 35.6% acknowledge the solution implemented as reasonable whereas only 35.5% consider the proposal for introducing gender parity as worth-implementing. Nevertheless the percentage of adversaries of such solutions is even smaller - in the case of quotas it is 28.1% and in the case of gender parity - 35.1%. The rest of the Law and Justice adversaries do not have an opinion on this issue. The division into adherents and adversaries of the decision about implementing statutory quotas or proposals for gender parity with reference to ideological views is even clearer. Among the respondents expressing their views as left- wing more than half of them acknowledge the implementation of quotas as reasonable (51%) and 38.5% consider the propo- sals for gender parity as worth- implementing. 48% of the persons sympathising with the centre were in favour of quotas, while 34% were for gender parity. On the other hand among the respondents defining their views as right-wing only 31.8% acknowledged the implementation of statutory quotas as reasonable whereas 29.8% considered the proposal for gender parity as worth-implementing. It is worth-emphasising that irrespective of political sympathies the respondents assess the implemented statutory quotas much favourably than the proposal for implementing gender parity on electoral lists.